Reduced Incidence of Slowly Progressive Heymann Nephritis in Rats Immunized With a Modified Vaccination Technique. Issue 1 (2006) - Barabas, Arpad Z.; Cole, Chad D.; Barabas, Arpad D.; Barabas, Aron N.; Lafreniere, Rene
Abstract : A slowly progressive Heymann nephritis (SPHN) was induced in three groups of rats by weekly injections of a chemically modified renal tubular antigen in an aqueous medium. A control group of rats received the chemically unmodified version of the antigen in an aqueous solution. One group of SPHN rats were pre- and post-treated with weekly injections of IC made up of rKF3 and rarKF3 IgM antibody at antigen excess (MIC) (immune complexes [ICs] containing sonicated ultracentrifuged [u/c] rat kidney fraction 3 [rKF3] antigen and IgM antibodies specific against the antigen, at slight antigen excess). One group of SPHN rats were post-treated with MIC 3 weeks after the induction of the disease and one group of SPHN animals received no treatment. The control group of rats received pre- and post-treatment with sonicated u/c rKF3. The incidence of immune-complex glomerulonephritis (ICGN) in the untreated SPHN rats was 87%, in the pre- and post-treated animals 13%, and in the post-treated-only rats 20%. Rats receiving sonicated ultracentrifuged rKF3 antigen did not develop ICGN. The present experiment demonstrates that the development of SPHN can be not only prevented but also effectively terminated by our newly developed modified vaccination technique.